Bargaining power as an economic force - Edgeworth, K. E. (Statistical and Social Inquiry Society of Ireland, 1936)
It is generally agreed that the results which are arrived at in economic theory are qualitative rather than quantitative, and the economist must often envy the exponents of the more exact sciences for the greater precision of the methods which they are able to employ. But even if it is not possible to express results in an exact form or to evaluate the precise significance of particular factors, it is none the less important that we should endeavour to create a mental picture of our economic problems which shall give a correct impression of the problems which we are trying to solve and which shall present the various items in the picture in their correct perspective. It is not, therefore, sufficient to decide whether a particular argument is valid or whether a particular method of approach is formally correct, we must go further and endeavour to arrive at a decision as to the relative importance of different factors in the situation, and alternative methods of approach must be judged by their power to discriminate between what is significant and what is trivial or unimportant. The present paper sets out to discuss some aspects of the question of the prices at which different commodities and services are bought and sold, and the resulting rewards which fall to the lot of individuals and groups of individuals, and its purpose is to suggest that existing theory lays too much stress on what may be called the "doctrine of satisfaction" and not enough stress on what may be called bargaining power.
Read on Friday, 11th October, 1935
Keywords: Economic war; Bargaining power; 314.15